Application of Lime as a Natural Ingredient in Dishwashing Liquid Formulation - salitxay, timnoy; PHOMLASABOUD, Khantavanh; CHANTHEEVILAYPHONE, Amphone; BOUNVILAYSONE, Soulaseng; SIVILAY, Phisouda (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aimed to evaluate the physicochemical properties, sensory acceptance, of lime-based dishwashing detergents formulated using different recipes. Completely Randomized Design (CRD) with four formulations (F1, F2, F3, F4), three replications were used. Physiochemical properties (pH value, foam retention time, and foam stability) and sensory evaluation were evaluated. The results revealed that pH values ranged from 8.36 to 8.76, with the highest value was observed in F1 (8.76), followed by F2 (8.67), while the F4 showed the lowest pH value (8.36). Foam retention time was found as longest in F1 (50 min), followed by F4 (42.33 min). However, F3 obtained shortest foam retention time with 21 min. Foam stability was highest in F3 (100%), followed by F4 (86%), F1 (84.58%), and F2 (76.66%). Sensory evaluation was conducted with 30 panelists using 5-point hedonic scale. Most panelists were female (53.3%), aged 16-30 years (43.3%), with a monthly income of 2,000,000 – 4,000,000 LAK (50%). Among formulas, F4 received the highest sensory scores across all attributes overall liking, color, odor, viscosity, foam, cleaning efficiency, and after-washing feel with mean score ranging from 4.4 to 4.6. Overall product acceptance and purchase intention reached 100%, indicating strong consumer acceptance and high market potential for lime-based dishwashing liquid.